Working memory in children with down syndrome - Yusoff, Shaznee Iryana (2014)
Down syndrome, characterized by cognitive impairment, a number of physical characteristics such as small chin, slanted eyes, poor muscle tone, and a flat nasal bridge, Mongoloid- like facial and multiple deformities. The Down Syndrome (DS) or Trisomy 21 is a common chromosome disorder which has an extra chromosome on the 21st pair resulted in impairments and limitations in developmental abilities and physical growth as compared to normal children. Roughly, 1 in 700 to 800 live births (Sherman et al., 2007; Centers for Disease Control & Prevention, 2006) in western countries showed the incidence of Down syndrome while the total number of worldwide is more than 200,000 cases per year (Christianson et al., 2006). A survey conducted in a Maternity Hospital, Kuala Lumpur showed that the incidence of Down syndrome was 1:959 live births. The incidence of this chromosome disorder within the three major ethnics in Malaysia is 1:987 in Malay, 1:940 in Chinese and 1;860 in Indian(Hoe et al., 1989). Most individuals with Down syndrome have an IQ ranging from mild (IQ 50-70) to moderate (IQ 35-50) (Naess et al., 2011) and they are believed to be slow learners. Since it is commonly associated with mental retardation, impairments in the growth of cognitive development are inevitable.